The Influence Of Influencer Marketing And Brand Image On The Tiktok App On Fast Fashion Product Purchase Decisions - Indrawati, Indrawati; Nurbasary, Anny (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The emergence of social media, especially TikTok, changed the fashion industry. With this platform, influencer marketing and brand image have new opportunities to influence consumers’ decisions to buy fast fashion items. The study investigated how influencer marketing and brand image on the TikTok app influence consumers’ decisions to buy fast fashion products. The data was collected through an online survey conducted on 200 TikTok users in Bandung. Research shows that the influence of influencer marketing and brand image significantly influences consumers’ decision to buy something. In addition, there is a positive interaction between the two factors. This suggests that influencer marketing has a greater influence on purchasing decisions when brand image is positive. This research was conducted at Maranatha Christian University. The sample technique used in this study is non-probability sampling. The purpose of this study was to find out how the influence of Influencer marketing and Brand image on purchasing decisions in Fast Fashion at Maranatha Christian University. The data analysis techniques used are classical assumption test and multiple linear regression analysis. Data obtained from the questionnaire will be tested using IBM SPSS. The tests carried out are classical assumption tests (normality, heterokedasticity and multicolonicity) and multiple linear regression (t test, f test, and coefficient of determination). Based on the results of multiple linear regression tests on the T test, it can be concluded that Influencer marketing has an influence on the purchase decisions of fast fashion products because the value of t is calculated > t table. Based on the results of the multiple linear regression test on the T test, it can be concluded that brand image has an influence on purchasing decisions because the t value is calculated > t table. This means that the better the brand image built by a company, the higher the level of purchasing decisions for fast fashion products.